2009
DOI: 10.1021/jp904396j
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Kinetics of Graphene Oxide Determined by Electrical Transport Measurements and Temperature Programmed Desorption

Abstract: The thermal stability and reduction kinetics of graphene oxide were studied by measuring the electrical resistivity of single-layer graphene films at various stages of reduction in high vacuum and by performing temperature programmed desorption (TPD) measurements of multilayer films in ultrahigh vacuum. The graphene oxide was exfoliated from the graphite oxide source material by slow-stirring in aqueous solution, which produces single-layer platelets with an average lateral size of ∼10 µm. From the TPD measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
139
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(162 citation statements)
references
References 36 publications
19
139
3
1
Order By: Relevance
“…Graphite oxide can be easily dispersed as separate layers in water solution, deposited as thin films 10,[21][22] and converted into graphene by mild heat treatment, by reduction in solutions (see e.g. 6,9,[23][24] ) or even by light from a camera flash 25 . Several structural models have been proposed for GO based on NMR, XPS and IR spectroscopy data 4-,8,13,15,26-27 , and some of them suggest that epoxy, carbonyl and -OH groups X-rays are attached to the graphene skeleton which results in some buckling of the planes.…”
Section: Toc Figure Abstract High Pressure • Graphite Oxide • X-ray Dmentioning
confidence: 99%
“…Graphite oxide can be easily dispersed as separate layers in water solution, deposited as thin films 10,[21][22] and converted into graphene by mild heat treatment, by reduction in solutions (see e.g. 6,9,[23][24] ) or even by light from a camera flash 25 . Several structural models have been proposed for GO based on NMR, XPS and IR spectroscopy data 4-,8,13,15,26-27 , and some of them suggest that epoxy, carbonyl and -OH groups X-rays are attached to the graphene skeleton which results in some buckling of the planes.…”
Section: Toc Figure Abstract High Pressure • Graphite Oxide • X-ray Dmentioning
confidence: 99%
“…20 It readily exfoliates to thin sheets in water, segregates at the water-air interface upon solvent evaporation, 21 and could be easily processed into continuous paper-like lms. 22,23 Properties of rGO, such as conductivity, tensile strength, etc., strongly depend on the degree of GO reduction, 24,25 which means that they could be nely tuned by the reduction conditions. Rich chemistry of rGO allows for further chemical modication with different functional groups, 2,3 which potentially makes rGO a very versatile platform for gas sensing.…”
mentioning
confidence: 99%
“…The kinetic aspects of GO reduction processes have been addressed in a few papers only. In one of the above-mentioned works [5], the kinetics of resistance changes and a thermo-programmed desorption of gaseous products have been studied for a monolayer GO. The activation energy values calculated in that work were found to be 38±1 and 32±4 kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to their importance in many potential applications, the electrophysical properties of GO-based materials have received much attention recently. In a kinetic study of the monolayer sheet rGO's conductivity, it has been shown [5] that when raising the GO reduction temperature to 200…”
Section: Introductionmentioning
confidence: 99%